2017
DOI: 10.1016/j.jflm.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model in post-mortem estimation of brain edema using morphometric parameters

Abstract: Current autopsy principles for evaluating the existence of brain edema are based on a macroscopic subjective assessment performed by pathologists. The gold standard is a time-consuming histological verification of the presence of the edema. By measuring the diameters of the cranial cavity, as individually determined morphometric parameters, a mathematical model for rapid evaluation of brain edema was created, based on the brain weight measured during the autopsy. A cohort study was performed on 110 subjects, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 7 publications
(8 reference statements)
7
17
2
Order By: Relevance
“…To exclude the cranial height, as it is a nonstandard measure during autopsy, we multiply the resultant factor (0.429) by the mean of the height (12.59 cm), so the new factor was 0.429 × 12.59 = 5.4. This accords with the results of Radojevic et al, 4 who found the mean height (12.19 cm) and the ε ( h ) (5.79). The final equation was as follows:…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To exclude the cranial height, as it is a nonstandard measure during autopsy, we multiply the resultant factor (0.429) by the mean of the height (12.59 cm), so the new factor was 0.429 × 12.59 = 5.4. This accords with the results of Radojevic et al, 4 who found the mean height (12.19 cm) and the ε ( h ) (5.79). The final equation was as follows:…”
Section: Discussionsupporting
confidence: 93%
“…The diameters of the cerebral cavity were measured using a slide caliper in the central sagittal area, the transversal plane’s widest level, and the frontal plane for the depth. To determine the depth, a hole was drilled at the top of the skull, the obtaining portion of a slide caliper was pulled through it, and the length to the middle of the clivus of the occipital bone was measured 4 …”
Section: Methodsmentioning
confidence: 99%
“…They also found no significant correlation between increased brain weight and perivascular distension observed in histology slides (7). Radojevic et al very recently argued that not only the weight of the brain but also its volume plus that of the cranial cavity must be taken into account when evaluating potential brain edema (8). Berger et al had some success in diagnosing edema when using postmortem CT images to assess narrowing of the temporal horns and herniation of the cerebellar tonsils (9).…”
Section: Introductionmentioning
confidence: 99%
“…Radojevic et al introduced a coefficient calculated as ε=5.79(longitudinal distance in the skull)(transverse distance in the skull)/brain weight(8). The constant 5.79 takes into account both the height of the skull as well as the density of brain tissue as determined based on cases included in their study.…”
mentioning
confidence: 99%
“…Furthermore, other than organ weight, no quantitative indicators are available to connect the effects of variation in the TWC and the cause of death. 12 In the clinical medicine field, hematocrit is used to measure the ratio of erythrocyte flow to total blood flow. When the organs absorb water from the blood, hematocrit is expected to increase 13 ; however, to our knowledge, no previous reports have evaluated this relationship using an autopsy sample.…”
Section: Introductionmentioning
confidence: 99%